IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KELURAHAN (SIMKEL) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAGELANG PROVINSI JAWA TENGAH - Sri Hartati; Fairuz Nurma Hadina (Institut Pemerintahan Dalam Negeri, 2019)
he Village Administration Management Information System (Simkel) is a system aims to provide a database of population and civil registration data that is integrated with SIAK applications that same between village administration, subdistricts and the department of population and civil registration that online and connected to the website. This research was intended to understand and know how to implement Simkel and the obstacles and efforts did by the Department of Population and Civil Registration of Magelang City.The research method used in this final report is descriptive qualitative with an inductive approach. the data collected were analyzed using analysis techniques in the form of data presentation, data reduction and drawing conclusions referring the theory of George Edward III.Based on the analysis conducted by the writer, the implementation of the Village Administration Management Information System (Simkel) has not going well because there are still some obstacles including unstable networks, limited number of employees and application providers that have not worked optimally. Efforts made to overcome obstacles include coordinating, making minimum qualification letters for staff needs and coaching for employees. Keywords: implementation, Simkel